دراسة أثر تقلبات سعر صرف الدينار الجزائري على المستوى العام للأسعار في الجزائر دراسة قياسية 1990-2020 - رزق الله السعيد; سويح جمال (جامعة عمار ثليجي الاغواط, 2022)
The target of our study is to know the effect of fluctuations in the exchange rate of the Algerian dinar on the general level of prices in Algeria during the period (1990-2020), and to highlight the extent of the contribution of the exchange rate to the economy and how inflation rates effect it. That why, we combined the theoretical study and also the applied study, by analyzing the progress of the exchange rate and inflation rate in Algeria. After the study, we reached a set of results, among which there is a complementary relationship but partly, between the exchange rate of the Algerian dinar at the general level of prices, but partly according to the coefficient of determination of 0.32 and the study proved that became there are the factors that affect on the general level of prices: Like the collapse of oil prices, the monopoly...etc.